Comparison of the effectiveness of Gingival unit transfer and free Gingival graft in the management of localized Gingival recession - A systematic review - Chetana; Sangamithra Sidharthan; Gopalakrishnan Dharmarajan; Sonal Kale; Soniya Dharmadhikari; Dhakshay Chordia (Elsevier, 2023)
Background: Gingival Recession (GR) is defined as the displacement of the soft tissue margin apical to the cementoenamel junction which can lead to root exposure and hypersensitivity. Treatment of GR has become an important therapeutic issue due to the increasing number of cosmetic requests from patients. Several techniques exist for the management of GR that include Sub-Epithelial Connective Tissue Graft (SECTG), Pedicle Graft (lateral and coronal), and Free Gingival Graft (FGG) and more. FGG is a non-submerged grafting procedure carried out for the management of recession defects. However, FGG has limitations like aesthetic mismatch and bulky appearance. A relatively newer modification of FGG was introduced by Allen in 2004 wherein a palatal graft including the marginal gingiva and interdental tissue was used as donor tissue for recession coverage. This review aims to study and compare the use of Gingival Unit Graft/Transfer (GUG/GUT) (palatal graft including the marginal gingiva and papillae) and FGG in the management of GR. Materials and Methods: Randomized Clinical Trials, Non-Randomized Controlled Clinical Trials for the treatment of Miller Class I,II, and III of GRs by GUG with FGG were identified. Data sources included electronic databases and hand-searched journals. The primary outcome variables were complete root coverage, mean root coverage, vertical recession depth. The secondary outcome variables were keratinized tissue width gain, clinical attachment level and probing depth. Results: Three Randomized Control Trials (RCTs) met the inclusion criteria and were evaluated in this systematic review. Both techniques showed significant improvement in clinical parameters. GUG procedure resulted in a greater percentage of sites achieving complete root coverage and vertical recession depth reduction when compared to FGG group in all the studies. Two studies reported significantly greater mean root coverage in GUG group compared to FGG group. GUG procedure revealed statistically significant greater gain in keratinized tissue width when compared to FGG group in all the studies. Conclusion: Because of the limited number of selected studies, no conclusive statement could be made regarding the advantage of the GUG technique over FGG. However, the percentage of sites with complete root coverage obtained in the GUG technique is higher than FGG. More RCTs with aesthetic and patient satisfaction-related parameters are needed to provide definite evidence.